Establishing a System for Verifying Matriculation Exam in Polish Administrative Law: Selected Aspects - Łukasz Kierznowski (Institutiones Administrationis)
The secondary school leaving exam exists under various names and with varying characteristics across the globe. The Polish matriculation exam (“matura”) deserves special attention as it has assumed a new, external aspect since its overall reform in 2005. Unfortunately, the first years after the reform revealed a significant problem with its assessment: numerous cases of incorrectly graded papers have been reported which fueled large-scale social unrest as there was no procedure in place for appealing against the matura results. After more than ten years, the regulations were changed for the better, and a special body, the College of Examination Arbitration was installed. In this paper, I consider this historic development, and I offer a general treatment of its administrative and constitutional implications as to the educational rights and civic liberties within the Polish legal context.